1975
DOI: 10.1111/j.1365-2133.1975.tb03056.x
|View full text |Cite
|
Sign up to set email alerts
|

Post-inflammatory elastolysis and cutis laxa

Abstract: Post-inflammatory elastolysis and cutis laxa (Marshall, Heyl & Weber, 1966) is a skin disease in African infants which appears to be comparatively common in at least two countries. Destruction of elastic tissue and atrophy are preceded by urticarial or by annular erythematous-popular lesions and result in severe disfigurement. The clinical features are intermediate between anetoderma (macular atrophy) and acquired cutis laxa, but sufficiently typical and characteristic to constitute a distinctive syndrome, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
3

Year Published

1976
1976
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(35 citation statements)
references
References 8 publications
1
31
0
3
Order By: Relevance
“…54 Cases in persons of African or South American origin are most commonly reported, although one case in a child from North America has been reported. 85,86 The disorder appears to be more common in females than in males. There is typically no family history of postinflammatory elastolysis and cutis laxa.…”
Section: Acquired Cutis Laxamentioning
confidence: 96%
See 1 more Smart Citation
“…54 Cases in persons of African or South American origin are most commonly reported, although one case in a child from North America has been reported. 85,86 The disorder appears to be more common in females than in males. There is typically no family history of postinflammatory elastolysis and cutis laxa.…”
Section: Acquired Cutis Laxamentioning
confidence: 96%
“…It has been suggested anecdotally that postinflammatory elastolysis and cutis laxa may be the result of an idiosyncratic reaction to the bite of an arthropod. 86 It has also been suggested that the high prevalence among young children is consistent with an environmental cause, such as exposure to grass, vegetation, or insects.. 86 Alternatively, postinflammatory elastolysis and cutis laxa may be the result of an idiosyncratic reaction to ultraviolet or infrared radiation in genetically predisposed persons. 87 Clinical manifestations.…”
Section: Acquired Cutis Laxamentioning
confidence: 98%
“…It has been classified as either local ized or generalized, may be congenital or acquired, and with or without systemic involvement. Maghraoui et al [ 10) proposed a spectrum of acquired loss of elastic fibers including: (l) postinflammatory elastolysis and cutis laxa [14][15][16]; (2) postinflammatory elastolysis without cutis laxa [3][4][5][6], and (3) middermal elastolysis without inflammation or cutis laxa [7][8][9][10][11], Idiopathic middermal elastolysis predominantly affects middle-aged white women. There is usually no family his tory or systemic involvement.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Postinflammatory elastolysis, usually seen in African children as an abnormal reaction to an arthropod bite, produces clinical changes similar to elastoderma but, histologically, elastic fibers are absent in the papillary and middle dermis. 10,11 Several studies show that smooth muscle cells in culture synthesize relatively large quantities of elastin, suggesting that they may be the major source of elastin in tissues rich in elastic fibers, such as vascular connective tissue. In addition, human dermal fibroblasts in culture also express the elastin gene, and elastin production by culture fibroblasts has been demonstrate by immunoblotting with the use of antielastin antibodies and molecular hybridization of messenger RNA with elastin-specific probes.…”
Section: Discussionmentioning
confidence: 99%